Pentingnya Komunikasi Efektif dalam Pembelajaran Anak Usia Dini di TK Nurul Arafah - Annisa, Syafiqah; Anggraini, Elya Siska; Saragih, Nabila Riyani Amanda; Karina, Enda Rejekinta; Purba, Timotius (Universitas Negeri Padang, 2024)
Communication is a process of conveying information to someone, witheffective communication it can make it easier for someone to receiveinformation well. In learning, the need for effective communication is used by ateacher when explaining material to students. Therefore, a teacher mustcommunicate effectively in providing explanations of material to students sothat the language used to provide material to students is easy to understandand comprehend. Therefore, the researcher took the title the importance ofeffective communication in early childhood learning at Nurul ArafahKindergarten with the aim of finding out whether communication betweenteachers and students during learning was going well or not. By using aqualitative research method where the researcher produces descriptive data inthe form of written words and behavior observed during the research, namelyat Nurul Arafah Kindergarten. From the results, Nurul Arafah Kindergartenuses the lecture method in learning which is very effective for communicatingduring learning.